RGC-32 deficiency protects endothelial cell from inflammation and attenuates atherosclerosis - Cui, Xiao-Bing (Arterioscler Thromb Vasc Biol, 2018)
OBJECTIVE: The objective of this study is to determine the role and underlying mechanisms of response gene to complement 32 (RGC-32) in atherogenesis. APPROACH AND RESULTS: RGC-32 was mainly expressed in endothelial cells (ECs) of atherosclerotic lesions in both apolipoprotein E-deficient (ApoE(−/−)) mice and human patients. RGC-32 deficiency (Rgc32(−/−)) attenuated the high-fat diet-induced and spontaneously developed atherosclerotic lesions in ApoE(−/−) mice without affecting serum cholesterol concentration. Rgc32(−/−) appeared to decrease the macrophage content without altering collagen and smooth muscle contents or lesional macrophage proliferation in the lesions. Transplantation of wild-type (WT) mouse bone marrow to lethally irradiated Rgc32(−/−) mice did not alter Rgc32(−/−)-caused reduction of lesion formation and macrophage accumulation, suggesting that RGC-32 in resident vascular cells, but not the macrophages, plays a critical role in the atherogenesis. Of importance, Rgc32(−/−) decreased the expression of intercellular adhesion molecule 1 (ICAM-1) and vascular cell adhesion molecule 1 (VCAM-1) in ECs both in vivo and in vitro, resulting in a decrease in tumor necrosis factor (TNF)-α-induced monocyte-EC interaction. Mechanistically, RGC-32 mediated the ICAM-1 and VCAM-1 expression, at least partially, through nuclear factor (NF)-κB signaling pathway. RGC-32 directly interacted with NF-κB and facilitated its nuclear translocation, and enhanced TNF-α-induced NF-κB binding to ICAM-1 and VCAM-1 promoters. CONCLUSIONS: RGC-32 mediates atherogenesis by facilitating monocyte-EC interaction via the induction of endothelial ICAM-1 and VCAM-1 expression, at least partially, through NF-κB signaling pathway.